Primera cita de "Coquillettidia (Coquillettidia) richiardii" Ficalbi, 1899 (Diptera: Culicidae) para la Comunidad Valenciana - Rueda, Juan; Hernández, Ramón; Benavent, Joan Miquel; Sacco, Mattia; Benedito-Durà, Vicent (Universidad de Murcia, 2015)
First data of the Coquillettidia (Coquillettidia) richiardii Ficalbi, 1899 (Diptera: Culicidae) in the province of Valencia (Spain) In this study, we report the presence of mosquito larvae Coquillettidia (Coquillettidia) richiardii Ficalbi, 1899 (Diptera: Culicidae) in the pond called “mallada” in the Devesa located over an old sand bar separating the lake Albufera of Valencia from the Mediterranean Sea. Where 15 specimens distributed in two samples that were collected in summer of 2015.